Some Hexa-Coordinated Lanthanide(III) Iodide Complexes with Schiff Bases of Cyanoethylated benzaldehyde - Arora, Kishor; Sharma, Mukesh; Sharma, K.P. (Asian Journal of Chemistry, 2010)
A series of 16 new complexes of lanthanide(III) iodide, with the Schiff base ligands, 2-methyl- 4-NN-bis-2'- cyanoethylaminobenzylidineaniline [MCEABAB], 2-methyl-4-NN-bis-2'- cyanoethylaminobenzylidine p-chloro aniline [MCEABCAB], 2-methyl-4-NN-bis-2'- cyanoethylaminobenzylidine p-toludine [MCEABPT] and 2-methyl-4-NN-bis-2'- cyanoethylaminobenzylidine p-fluoroaniline [MCEABFAB] were synthesized. The complexes were characterized on the basis of elemental analyses, molecular weight determinations, conductivity measurements, IR spectra and electronic spectra. Mass spectra and TGA studies for the formation of complexes with general formula [Ln(L)4I2]I, [where Ln = La, Ce, Sm and Gd; L = MCEABAB, MCEABCAB, MCEABPT and MCEABFAB] were analyzed. Some of the synthesized complexes were tested for biological activity against a variety of test organisms, a few of them were found to be moderately effective.